The Effect of Design Thinking Applicaiton on Business Model Innovation at PT. RAPP with Creativity of Kaizen Team as Intervening Variable - Asysyhfa, Nisa (Politeknik Negeri Bengkalis, 2024)
Business model innovation is one of the key factors in the success of a business. Design thinking is a human-centred approach to problem solving and innovation, has gained significant attention as a methodology that can foster creativity, collaboration and customer centricity in the innovation process. This study seeks to investigate the effect of design thinking application on business model innovation at Riau Andalan Pulp and Paper (PT. RAPP), with the aim of understanding how design thinking can contribute to the development of innovative business models in this specific context. This involves using statistical methods such as hypothesis testing, regression analysis to identify significant relationships or influences between variables related to the influence of design thought and business model innovations in PT. Based on the test results conducted between the design thinking variable and the creativity of the kaizen team variables, it can be concluded that design thinking has a positive and significant effect on the creativeness of the team. It can also be found that the creative ability of the group mediates the relationship between the variable design thinking and the variable innovation variable.